A Novel User Collusion-Resistant Decentralized Multi-Authority Attribute-Based Encryption Scheme Using the Deposit on a Blockchain. (7th July 2021) - Noh, Siwan; Kim, Donghyun; Cai, Zhipeng; Rhee, Kyung-Hyune
Abstract : Recently, the concept of a decentralized data marketplace is getting much attention to exchange user data. Multi-authority attribute-based encryption (ABE), which can provide flexibility and user-centric access control, is previously widely used in decentralized data sharing applications and also becoming a foundation to build decentralized data trading applications. It is known that users in a multi-authority ABE system can collude by sharing their secret information for malicious purposes. To address this issue, the collusion-resistant multi-authority ABE model was introduced in which a unique global identifier (GID) is issued by the central authority (CA) to each user. Unfortunately, such approach cannot be used directly to build a decentralized data marketplace as (a) such intervention of the CA is directly against the main motivation of the decentralized trading platform and, mostly importantly, (b) the CA can exploit its full knowledge on users' GID to launch various attacks against users. Motivated by these observations, this paper introduces a novel user collusion-resistant decentralized multi-authority ABE scheme for privacy preserving data trading systems. In the existing multi-authority ABE systems, users utilize his/her GID that is solely assigned by the CA to generate his/her secret keys throughout the collaboration with authorities and a user can compute multi-authority keys by combining the secret keys (stem from the same GID) in various ways. In the proposed system, the CA only has a partial knowledge of users' GIDs, and thus, users' privacy can be protected. On the other hand, we set the user's own partial GID as a secret which can be used to withdraw his/her deposit to discourage any possible collusion among users.